Enhancing ESP Vocabulary Proficiency through Five Elements of Online Cooperative Learning for Nursing Students - Sofyan, Wini Fitrina; Agustini, Aat; Wati , Eti (The Institute of Research and Community Service (LPPM) - Universitas Lancang Kuning, 2024)
The widespread adoption of online learning has significantly transformed the dynamics of cooperative learning. One of the main challenges in distance cooperative learning is determining whether Online Cooperative Learning (OCL) can successfully elicit the fundamental elements of cooperative learning and, in turn, improve student learning outcomes. This study aims to examine whether the five essential elements of cooperative learning-positive interdependence, individual accountability, social skills, group processing, and face-to-face interaction-can emerge in a virtual environment and contribute to improving nursing students' proficiency in ESP (English for Specific Purposes) vocabulary. Using a quasi-experimental one-group design, this quantitative research involved 30 nursing students from a university in West Java, Indonesia, selected through convenience sampling. Paired t-test analysis was conducted to assess the impact of OCL. The comparison of pre-test and post-test values indicated that the five cooperative elements were effectively elicited, leading to enhanced student proficiency. The t-test yielded a t-value of 4.781, which surpassed the critical t-table value of 1.697, confirming a statistically significant improvement. These findings suggest that the OCL model successfully fosters the fundamental elements of cooperative learning and enhances nursing students’ ESP vocabulary proficiency. Consequently, this model presents a promising approach for improving ESP vocabulary skills in nursing education.